2019
DOI: 10.1093/ofid/ofz360.1964
|View full text |Cite
|
Sign up to set email alerts
|

2286. Evaluating the Impact of Ceftolozane/Tazobactam on Clinical Outcomes in Patients with Multi-Drug-resistant Pseudomonas aeruginosa Pneumonia

Abstract: BackgroundCeftolozane/tazobactam is a novel cephalosporin and β-lactamase inhibitor antibiotic that has shown to have potent activity against Pseudomonas aeruginosa including strains exhibiting multi-drug resistance (MDR). The purpose of this study was to evaluate ceftolozane/tazobactam efficacy in MDR P. aeruginosa pneumonia compared with historical standard of care.MethodsThis was a retrospective cohort study of patients hospitalized across AdventHealth Central Florida campuses with MDR P. aeruginosa pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…Of the 33 studies included in the SLR that included data on patients with RTIs (and presented outcomes for these patients), 28 were published as peer-reviewed publications, and ve were available as conference proceedings (either as abstracts or posters). [43][44][45][46][47] Including studies that included patients from multiple different countries, the most common study locations were the US (23 studies), 15,21,24-33,35−37,39-41,43−47 Spain (5), 20,22,23,36,42 and Italy (3). 15,18,19 There was a mix of study designs included: of nine non-comparative studies, eight were retrospective, 18,19,23,24,31,36,43,46 and one was prospective.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 33 studies included in the SLR that included data on patients with RTIs (and presented outcomes for these patients), 28 were published as peer-reviewed publications, and ve were available as conference proceedings (either as abstracts or posters). [43][44][45][46][47] Including studies that included patients from multiple different countries, the most common study locations were the US (23 studies), 15,21,24-33,35−37,39-41,43−47 Spain (5), 20,22,23,36,42 and Italy (3). 15,18,19 There was a mix of study designs included: of nine non-comparative studies, eight were retrospective, 18,19,23,24,31,36,43,46 and one was prospective.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Five studies were identi ed that compared C/T with other treatment regimens (Table 4): three included aminoglycoside/polymyxin-based regimens as comparator; (23,27,80) two either used standard of care (SoC). (26,83) Each study included patients with P. aeruginosa infections, with four including patients with resistant P. aeruginosa. (23,27,80,83) In the three studies with aminoglycoside-/polymyxin-based comparators, all reported mortality rates, (23,27,80) two reported clinical cure rates, (23,27) and one reported microbiological cure rate.…”
Section: Comparative Studiesmentioning
confidence: 99%
“…Including studies that recruited patients from multiple countries, the most common study locations were the US (N = 50), (21, 22, 24, 27-29, 33, 34, 39-41, 43-45, 50, 51, 54, 56, 57, 59, 61, 62, 68-71, 73-77, 79-85, 87-92, 94, 95, 97-100) Spain (N = 15), (26, 28, 30-32, 35-37, 42, 47, 49, 58, 66, 79, 96) and Italy (N = 13). (18,20,23,25,48,52,53,55,64,67,72,79,86) A variety of study designs were captured: 27 were non-comparative retrospective studies, (18,19,22,24,25,28,32,33,40,41,79,81,(84)(85)(86)(87)(88)(89)(90)(91)(92)(94)(95)(96)(97)(98)(99) 14 were case series, (20, 21, 29, 31, 34-39, 42, 43, 82, 100) ve were comparative (including two cohort studies, (80,83) and three case-control studies, (23,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations